Coincidence theorems for nonlinear hybrid contractions - Y. J. Cho; B. Fisher; G. S. Genga (International Journal of Mathematics and Mathematical Sciences)
In this paper, we give some common fixed point theorems for single-valued mappings and multi-valued mappings satisfying a rational inequality. Our theorems generalize some results of B. Fisher, M. L. Diviccaro et al. and V. Popa.